Development of an Augmented Reality–Integrated E-Module for Magnetic Induction: A Validity and Practicality Study - Yulianda, Hanny; Hasanah, Lilik; Suwarma, Irma Rahma (Universitas Islam Negeri Raden Intan Lampung, 2026)
Low mastery of physics concepts and limited availability of instructional media capable of visualizing abstract content remain persistent challenges among senior secondary school students. This study aimed to analyze the validity and practicality of an AR-integrated e-module developed for magnetic induction instruction at the senior secondary school level, as well as to examine its preliminary effectiveness in improving students’ conceptual mastery. Employing a Research and Development (R&D) approach guided by the Borg and Gall model with the ADDIE instructional design framework — encompassing analysis, design, development, implementation, and evaluation — this study collected data via expert validation sheets, practicality questionnaires, and pre-test/post-test concept mastery instruments analyzed using the Rasch model. The product is an Android-based AR-integrated e-module comprising learning instructions, concept maps, magnetic induction material, AR simulations, practice questions, interactive quizzes, summaries, evaluations, and a glossary. Media and material expert validation yielded average scores of 89.16% and 88.0%, respectively, both classified as ‘Good’. Practicality analysis from student responses (80.1%) and teacher responses (97.9%) confirmed that the media is highly practical and accessible for use in learning activities. Effectiveness was preliminarily measured through the Normalized Gain (N-Gain) index, yielding an average score of 0.69, classified in the medium category according to Hake’s (1998) criteria. These findings confirm that the AR-integrated e-module constitutes a valid, practical, and preliminarily effective learning resource with strong potential to support visualization of abstract magnetic induction concepts and enhance students’ conceptual understanding in physics education.